Biologia reprodutiva do pacu Myleus Micans (Lütken, 1875) (Characidae : Serrasalminae) do rio São Francisco, região de Três Marias, Minas Gerais - Santiago, Kleber Biana (2006)
The objective of this work was to study the reproductive biology of pacu (Myleus micans, Lütken, 1875) from San Francisco River, in Three Marias region, Minas Gerais, Brazil. Reproductive studies are important tools to understand natural processes which regulates a population, considering the low level of knowledge on the biology of this species. A total of 363 fishes were collected in this work, 169 males and 194 females, captured monthly, from June 2002 to May 2003, in a 5km area in San Francisco River, between the Hidreletric Plant (UHE) and the "Great Waterfall". Data on rain precipitation and water parameters (temperature, oxygen, and pH), were obtained during period of fish collection. Morphologic description of testicules and ovaries, and gametogenese process (spermeogenese and ovogenese), determination of gonadal maturation stages and type of spawning were performed. Hystological analyses, as well as, quantitative analysis of the reproductive activity (biological indices), standard weight/length relation, and population structure (sexual ratio) were done. The results has shown that morphologic variations in M. micans testicules, during the reproductive process are related to gonadal maturation stages, and morphologic characteristics of ancestry espermatogenics cells had been similar to other Brazilian bone fishes. Macroscopic analyses of ovaries had shown that this species has morphologic and anatomical similarity to other Brazilian bone fishes. Anatomical variations in the ovaries observed in some other species had not been verified. Post-ovulatories or empty folicules in M. micans were probably originary from hipertrophic process of foliculares cells, and folicular atresia was frequently observed. Six gonadal maturation stages in males and five in females had been identified. The weight-length relation for males and females of M. micans was: Wt = 2,68 x 10-2. Lt2,91(r2 = 0,989). The studied population presented alometric growth (b < 3). The population structure showed a ratio of 53,44% of females and 46.56% of males, approximately 1:1.